Large-scale self-organized gold nanostructures with bidirectional plasmon resonances for SERS. Issue 40 (21st June 2018) - Schreiber, Benjamin; Gkogkou, Dimitra; Dedelaite, Lina; Kerbusch, Jochen; Hübner, René; Sheremet, Evgeniya; Zahn, Dietrich R. T.; Ramanavicius, Arunas; Facsko, Stefan; Rodriguez, Raul D.
Abstract : Here we present a two-step fabrication of large-scale self-organized gold nanostructures for multicolor surface-enhanced Raman spectroscopy (SERS). We studied the morphology and plasmonic responses of our substrates and performed optical simulations. Abstract : Efficient substrates for surface-enhanced Raman spectroscopy (SERS) are under constant development, since time-consuming and costly fabrication routines are often an issue for high-throughput spectroscopy applications. In this research, we use a two-step fabrication method to produce self-organized parallel-oriented plasmonic gold nanostructures. The fabrication routine is ready for wafer-scale production involving only low-energy ion beam irradiation and metal deposition. The optical spectroscopy features of the resulting structures show a successful bidirectional plasmonic response. The localized surface plasmon resonances (LSPRs) of each direction are independent from each other and can be tuned by the fabrication parameters. This ability to tune the LSPR characteristics allows the development of optimized plasmonic nanostructures to match different laser excitations and optical transitions for any arbitrary analyte. Moreover, in this study, we probe the polarization and wavelength dependence of such bidirectional plasmonic nanostructures by a complementary spectroscopic ellipsometry and Raman spectroscopy analysis. We observe a significant signal amplification by the SERS substrates and determine enhancement factors of over a thousand times. We also perform finite element method-based calculations of the electromagnetic enhancement for the SERS signal provided by the plasmonic nanostructures. The calculations are based on realistic models constructed using the same particle sizes and shapes experimentally determined by scanning electron microscopy. The spatial distribution of electric field enhancement shows some dispersion in the LSPR, which is a direct consequence of the semi-random distribution of hotspots. The signal enhancement is highly efficient, making our SERS substrates attractive candidates for high-throughput chemical sensing applications in which directionality, chemical stability, and large-scale fabrication are essential requirements.